Theoretical Foundations of Historical Materialism for an Image Aesthetics in Mesoamerican Societies - Márquez Lorenzo, Emmanuel (Escritura e Imagen, 2021)
This work aims to present a series of theoretical foundations useful for the construction of a model, which can be used as an axis to address image studies of Mesoamerican societies. This model has been developed based on a critical posture of historical materialism, and is supported together, in an anthropological vision that emphasizes the mode of human perception based on its productive activities, considering the image as one of them. In the end, it is proposed to give interest to magical religious manifestations of ritual spaces, from a point of view that emphasizes the scope of ideologies within consumption spheres.
Keywords: archeology; aesthetics; ideology; politics; religion; ritual spaces